Factors Affecting Unused Remaining Volume of Intravenous Patient-controlled Analgesia in Patients Following Laparoscopic Gynecologic Surgery - Kim, Kyoung Ok; Roh, Ju-Won; Shin, Eun Jung; In, Junyong; Song, Tae Hun (Asian nursing research, 2014)
This study was undertaken to evaluate the factors affecting the unused remaining volume of intravenous patient-controlled analgesia (IV PCA) in patients who had undergone laparoscopic gynecologic surgery. We retrospectively collected patient records from pre-existing PCA log sheets from 98 patients. Surgical factors and IV PCA-related data including remaining volume, administration duration, early discontinuation (yes or no), and adverse reactions were recorded. Chi-square test, one-way analysis of variance, and multiple linear regression were applied for data analysis. The average age of the 98 patients was 40.0 ± 8.24 years. The incidence of postoperative nausea and vomiting (PONV) and early discontinuation were not statistically significant among the different surgical groups (p = .540 and p = .338, respectively). Twenty-eight patients wanted discontinuation of IV PCA and the remaining volume was 33.6 ± 7.8 mL (range 20-55 mL). The significant determinants of remaining volume were whether IV PCA was discontinued due to PONV and duration of surgery (p < .001). The surgical duration was inversely correlated with the remaining volume. Early discontinuation of IV PCA due to PONV is a major contributing factor to wastage of medicine. Prevention and treatment of PONV is needed to encourage patients to maintain PCA use for pain control.